The Knowledge and Practice of Breast Cancer Screening Among Women in Kerman, Iran - Narges Khanjani; Atefeh Noori; Fereshteh Rostami (Al Ameen Medical College, 2012)
Introduction: Breast cancer is the most common cancer in women, and if diagnosed on time, the chance of treatment will increase. There is limited information about the knowledge and practice of Iranian women about early detection of breast cancer and in this study we aimed to investigate it in Kerman. Methods: This was a cross-sectional study done on 120 women; from 6 randomly selected maternal and childcare centers spread around Kerman, women were questioned about the primary signs of breast cancer and the screening methods. Results: The results show that 70% of women thought that with on time detection, breast cancer can be successfully treated, but 47% had no idea about any screening method. The most common breast cancer sign mentioned by women was a painless lump. Breast self examination as the easiest and cheapest screening method was never done in 51% of women. The most common reason for not performing screening tests in the participants, was not knowing anything about it. Conclusion: Although breast cancer when diagnosed on time is treatable, the knowledge and attitude of Iranian women about breast cancer screening and the signs of breast cancer are very low. Educational programs to increase women's knowledge about breast cancer should be foreseen and performed